2016
DOI: 10.1111/fwb.12849
|View full text |Cite
|
Sign up to set email alerts
|

Biotic resistance buffers the effects of nutrient enrichment on the success of a highly invasive aquatic plant

Abstract: Summary Biotic resistance theory predicts that the presence of a species‐rich native community is able to inhibit the establishment of invasive species. On the other hand, disturbed environments, for example, through eutrophication, tend to be more easily invaded. We investigated the effect of biotic resistance on the establishment success of the aquatic grass Urochloa arrecta in nutrient‐enriched and non‐enriched mesocosms so as to test the hypothesis that the effects of biotic resistance on invader success… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 35 publications
0
16
1
Order By: Relevance
“…The density of plants in a community also determines competition intensity and the efficiency to exploit available resources and space (Naeem et al 2000;Teixeira et al 2017;Turnbull et al 2010;Wu et al 2017). Denser communities thus should leave less resources and space for potential invaders (Dostál 2011;Dukes 2002;Michelan et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The density of plants in a community also determines competition intensity and the efficiency to exploit available resources and space (Naeem et al 2000;Teixeira et al 2017;Turnbull et al 2010;Wu et al 2017). Denser communities thus should leave less resources and space for potential invaders (Dostál 2011;Dukes 2002;Michelan et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…, Tabassum and Leishman , Teixeira et al. ). The net effect of nutrient availability on species invasions will depend on characteristics of the invasive species (e.g., resource needs, resource use efficiency, trophic position) and the invaded ecosystem (e.g., relative roles of top‐down versus bottom‐up factors in regulating community dynamics; Kolar and Lodge , González et al.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the common co-occurrence of nonnative species and elevated nutrient loading, predicting how these two factors interact to drive ecosystem change remains a key challenge (Flores-Moreno et al 2016, Tabassum and Leishman 2016, Teixeira et al 2017. The net effect of nutrient availability on species invasions will depend on characteristics of the invasive species (e.g., resource needs, resource use efficiency, trophic position) and the invaded ecosystem (e.g., relative roles of top-down versus bottom-up factors in regulating community dynamics; Kolar andLodge 2000, Gonz alez et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, as in the first scenario, the species were left to grow for an additional 30 days after adding shading. We determined that the interval of 30 days between the planting of the native propagules and the addition of the propagules of the invasive species was sufficient because previous investigations conducted in the field with P. pernambucense (Milne, Murphy & Thomaz ) and in mesocosms with L. hexandra (Teixeira, Bini & Thomaz, in press) showed that these two species reach maturity between 45 and 50 days. This fast growth was confirmed in our experiment because the height and biomass were 73·8 cm (±16·24 SD) and 1·85 g DW (±16·24 SD), respectively, for P. pernambucense and 50·6 cm (±15·95 SD) and 1·54 g DW (±0·17 SD), respectively, for L. hexandra , after 30 days.…”
Section: Methodsmentioning
confidence: 99%